Unraveling the complex interplay: self-esteem, impostor phenomenon, proactive personality, and their influence on career satisfaction - Taşkıran, Erkan; Çelik, Gülşah Gençer; Behram, Nihal Kartaltepe; Elmalı, Esra Dinç; Öngel, Gökten (Frontiers in Psychology, 2025)
BackgroundBased on Social Identity Theory (SIT) and Self-Determination Theory (SDT), this study proposed a moderated mediation model in which the impostor phenomenon was established as an intervening instrument that highlighted why employees were more likely to be satisfied with their careers under the existence of self-esteem, and the indirect effect of self-esteem on career satisfaction via the impostor phenomenon was conditional on proactive personality.MethodsThe data required to fulfill the study’s purpose were collected through the survey technique. Employees (N = 376) working in customer relations, branch banking support, commercial transactions, etc., units at the head office of a well-known private bank operating in Istanbul, Turkey, were surveyed.ResultsThe findings obtained from the study revealed that self-esteem has a positive effect on career satisfaction and a negative impact on the impostor phenomenon. It was also found that the impostor phenomenon has a negative effect on career satisfaction. Moreover, it was discovered that the impostor phenomenon has not mediated the relationship between self-esteem and career satisfaction. However, a proactive personality has moderated the effect of the impostor phenomenon on career satisfaction. Furthermore, a proactive personality moderated the indirect effect of the impostor phenomenon on the relationship between self-esteem and career satisfaction.ConclusionThis study underscores a novel intersection of psychological constructs -self-esteem, the impostor phenomenon, and proactive personality- and their profound implications for career satisfaction, bringing us one step closer to understanding the complex dynamics of employee satisfaction within the professional realm.